If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8x-9=7x-7
We simplify the equation to the form, which is simple to understand
8x-9=7x-7
We move all terms containing x to the left and all other terms to the right.
+8x-7x=-7+9
We simplify left and right side of the equation.
+1x=+2
We divide both sides of the equation by 1 to get x.
x=2
| -64x^2+120x-42=0 | | 3(a+2)+4a=2(a-7) | | -4f-(-8)=4f+(-8) | | 0.4x+3=0.3x | | 5x-1.3= | | h=-4.9x^2+60x+38 | | 2x+10=x+86 | | x=2(6+2)(5-3) | | 7t+6t=13t | | 3y-15=y-15 | | n+2n+3n+(4+5)n+6(7+2n)= | | 6[5-(8x-9)]+7x=0 | | -5*x-1=-9 | | 4x=4x+134 | | 6z+6+2z-4=90 | | x*-5-1=-9 | | -4g+5=-7g-10 | | 4-9[7-(8x-8)]= | | 17-9x=80 | | h^2-h+42=0 | | u=72 | | 3x^2+7x+11=0 | | T+12=-4 | | 7r-3r=31r-2 | | a(a-5)=14 | | 2=72n^2 | | Y-12=-4 | | 4x+y=-30 | | 142=96+46 | | x+x+3+x=33 | | 2=-16t^2+22t+10 | | 3(1-3x)=(-4x+7) |